Judgement, decision making and success in sport - Bar-Eli, Mikhaʾel; Plessner, Henning; Raab, Markus (Wiley, 2011)
Judgement, Decision Making and Success in Sport; Contents; Preface; Judgement and Decision Making as a Topic of Sport Science; Maximization and optimization in sport; JDM history; The development of JDM research in sport; Rationale and structure of this book; Theories of (Social) Judgement; Psychophysics; Social judgement theory; Social cognition; Summary; Theories of Decision Making; Subjective expected utility theory; Prospect theory; Decisional field theory; Simple heuristic approach; Summary; Expertise in JDM; What are the components of expertise in JDM?; How can we measure JDM expertise?
Description based upon print version of record
Keywords: Electronic books; Sportpsychologie; Entscheidungsfindung; Urteilen